HUBUNGAN ANTARA REGULASI DIRI DENGAN KEMANDIRIAN BELAJAR SISWA KELAS X SMA LABORATORIUM UNIVERSITAS PGRI SEMARANG - Anisa Hayyu Hanifah; Suhendri; Chr. Argo Widiharto (STKIP Subang, 2023)
The research was motivated by several problems, namely: (1) students have low self-regulation which is addressed in their behavior, such as: not having a plan for studying, being disappointed in receiving low grades given by the teacher, and forgetting the study schedule. Students also have low learning independence which is reflected in their behavior, such as: being less active when learning takes place, easily asking other friends for answers, and lacking self-confidence. The aim of the research is to determine the relationship between self-regulation and student learning independence. The research uses a quantitative approach. The design used is a survey research design. The population of this study was all students in class X1 at the PGRI University Semarang Laboratory High School, totaling 26 students as well as the research sample. The sampling technique uses a saturated sampling technique. Data collection techniques use non-test techniques with a self-regulation scale and a learning independence scale. The data analysis technique uses descriptive statistics. Hypothesis testing using the Pearson correlation test using SPSS.26. The research results show that there is a relationship between self-regulation and learning independence with a 2-tailed significance value of 0.000 <0.05, so it can be said to be correlated. The degree of relationship between the self-regulation variable and learning independence in the Pearson correlation test with a Pearson Correlation value of 0.728 > 0.61, then the self-regulation variable and the learning independence variable are correlated in the strong category in the form of a positive relationship. It can be concluded that there is a positive and significant relationship between self-regulation and the learning independence of class X students at the PGRI University Semarang Laboratory High School. The higher the self-regulation variable, the higher the learning independence variable.